2009
DOI: 10.1038/nnano.2009.77
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy detects differences in the surface brush of normal and cancerous cells

Abstract: The atomic force microscope is broadly used to study the morphology of cells1–5 but it can also probe the mechanics of cells. It is now known that cancerous cells may have different mechanical properties than normal cells6–8 but the reasons for these differences are poorly understood9. Here we report quantitatively the differences between normal and cancerous human cervical epithelial cells by considering the brush layer on the cell surface. These brush layers, which consist mostly of microvilli, microridges, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
388
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(408 citation statements)
references
References 27 publications
16
388
4
Order By: Relevance
“…The potential specificity of nanoparticles to attach to diseased cells as against healthy cells [136] offers selectivity, and the use of ROS or RNS carried by nanoparticles as the main agent against either cancer cells or pathogens reduces the reliance on toxic materials (e.g. silver).…”
Section: Synergy In Reaction Chemistrmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential specificity of nanoparticles to attach to diseased cells as against healthy cells [136] offers selectivity, and the use of ROS or RNS carried by nanoparticles as the main agent against either cancer cells or pathogens reduces the reliance on toxic materials (e.g. silver).…”
Section: Synergy In Reaction Chemistrmentioning
confidence: 99%
“…It is known that nanoparticles may preferentially deposit near cancer cells rather than healthy cells [136]. Therefore a combined use of plasmas and nanoparticles is likely to enhance the directionality of the propagation of both plasma species and nanoparticles towards diseased sites within a tissue.…”
Section: Synergy For Enhanced Penetration and Selectivitymentioning
confidence: 99%
“…When a normal cell transforms into a cancerous cell, its structures and functions change considerably (Hanahan and Weinberg, 2011). For example, cellular surface brush layers (mainly consisting of microvilli, microridges and cilia) between normal cells and cancerous cells differ significantly (Iyer et al, 2009). Here, we can observe the significant differences between normal breast cells and cancerous breast cells in several aspects, including cellular growth, cellular shape, cellular edge and cellular geometric features.…”
Section: Rusults and Discussionmentioning
confidence: 99%
“…40 Moreover, it has been demonstrated that it is possible to detect length and grafting density of the brush layer on living cells, 65,66 or even to distinguish between cancerous and healthy cells' brushes, 67 thanks to the sensitivity of micrometric spherical probes provided by their wider surface area.…”
Section: Colloidal Spherical Probesmentioning
confidence: 99%